Hubungan Pengetahuan dan Sikap Pasangan Usia Subur Tentang Kesehatan Reproduksi Keluarga Berencana di Wilayah Kecamatan Tabunganen - Sri Jamilah; Sri Purwanti Ariani; Putri (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
Men and women have equal rights to access information and receive equal opportunities in meeting reproductive health needs. Efforts to promote reproductive health are not solely an individual concern but also a family responsibility. Gender equality and male responsibility in relation to reproductive health and Family Planning (FP) represent a new paradigm within the FP program, established through the Cairo Agreement of 1994. One challenge in increasing male participation in FP efforts is the ongoing misconception in society that tends to make women the primary focus of reproductive health issues. This may be due to a lack of family knowledge about women's reproductive health issues.